2012
DOI: 10.14417/ap.105
|View full text |Cite
|
Sign up to set email alerts
|

Tradução e validação da Escala de Resiliência para Estudantes do Ensino Superior

Abstract: O conceito de resiliência, enquanto capacidade do indivíduo manifestar uma adaptação positiva em face de situações adversas, tem interessado, nas últimas décadas, os investigadores que procuram compreender os percursos de desenvolvimento em situações de risco ou vulnerabilidade. Num âmbito mais restrito, alguns autores têm tentado criar instrumentos que capturem a percepção que os sujeitos têm de serem (ou não) capazes de enfrentar situações difíceis ou potencialmente stressantes. Nesta linha, a Resilience Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 19 publications
4
28
0
9
Order By: Relevance
“…24 This growth, although different in each age group, revealed, and corroborated the narrative analysis, a positive influence of intergenerational relationships on academic performance in both groups. Studies have shown the importance of a variety of family relationships between young and old individuals.…”
Section: " (Ei1)supporting
confidence: 72%
“…24 This growth, although different in each age group, revealed, and corroborated the narrative analysis, a positive influence of intergenerational relationships on academic performance in both groups. Studies have shown the importance of a variety of family relationships between young and old individuals.…”
Section: " (Ei1)supporting
confidence: 72%
“…When compared with the classification of Wagnild and Collins (2009), we can conclude that they are integrated in the moderate level of resilience (121 to 145). Oliveira and Machado (2011), in a sample with similar characteristics, of 451 polytechnic education students found a lower global average then the present study (128.9±16.4). Analysing the average value of each factor, we highlight as higher the result in the selfdiscipline dimension (5.90±.81) followed by autonomy (5.70±.87), personal skills (5.69±.88) and problem solving (5.77±.82).…”
Section: Resultssupporting
confidence: 54%
“…The Portuguese Version of the Resilience Scale (Oliveira & Machado, 2011) is a self-report instrument, composed of 25 items, organized accordingly with a Likert type scale of 7 points (1-totally disagree, 4-neither agree or disagree and 7-totally agree with the statement), ranging from 25 to 175, with higher scores indicating higher resilience. Items comprise questions related to the subject (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The roots for resilience are created in childhood and in adulthood resilience may increase, stemming from, in such cases, the effect of past successes in dealing with adversity (Oliveira & Machado, 2011). Jowkar (2014) mentions that resilience has been conceptualized as an individual characteristic and http: //dx.doi.org/10.15405/ejsbs.211 eISSN: 2301-2218 …”
Section: Introductionmentioning
confidence: 99%